DICER1 and FOXL2 Mutation Status Correlates With Clinicopathologic Features in Ovarian Sertoli-Leydig Cell Tumors. (May 2019) - Karnezis, Anthony N.; Wang, Yemin; Keul, Jacqueline; Tessier-Cloutier, Basile; Magrill, Jamie; Kommoss, Stefan; Senz, Janine; Yang, Winnie; Proctor, Lily; Schmidt, Dietmar; Clement, Philip B.; Gilks, C. Blake; et al.
Abstract : Sertoli-Leydig cell tumors (SLCTs) are rare ovarian sex cord-stromal neoplasms. The only known recurrent genetic abnormality is DICER1 mutation, with rare mutations reported in FOXL2 . We set out to establish a molecular classifier using DICER1 and FOXL2 somatic mutation status and clinicopathologic features in 42 SLCTs. Five tumors (12%) were well differentiated, 31 (74%) moderately differentiated, and 6 (14%) poorly differentiated. Eight (19%) had heterologous elements, and 2 (5%) showed retiform differentiation; all 10 were moderately differentiated. DICER1 RNase IIIb domain mutations were identified in 18/41 (44%; 17 moderately, 1 poorly differentiated), including all cases with retiform or heterologous elements. FOXL2 c .402C>G (p.C134W) mutation was identified in 8/42 (19%) tumors (5 moderately, 3 poorly differentiated). DICER1 and FOXL2 mutations were mutually exclusive. Median age for the cohort was 47 years (range, 15 to 90 y). Patients with DICER1 mutations were younger (median, 24.5 y; range, 15 to 62 y) than patients with FOXL2 mutation (median, 79.5 y; range, 51 to 90 y) ( P <0.0001). Nine of 10 tumors with retiform or heterologous elements occurred in premenopausal patients (median, 26.5 y; range, 15 to 57 y). Patients with tumors that were wild type for DICER1 and FOXL2 (15/42, 37%) had an intermediate age (median, 51 y; range, 17 to 74 y). All tumors were FOXL2 positive by immunohistochemistry. Patients with FOXL2 mutation trended toward presenting more often with abnormal bleeding ( P =0.13); DICER1 -mutant patients trended toward having more androgenic symptoms ( P =0.22). Our data suggest at least 3 molecular subtypes of SLCT with distinct clinicopathologic features: DICER1 mutant (younger, more androgenic symptoms, moderately/poorly differentiated, retiform or heterologous elements), FOXL2 mutant (postmenopausal, abnormal bleeding, moderately/poorly differentiated, no retiform or heterologous elements), and DICER1 / FOXL2 wild type (intermediate age, no retiform or heterologous elements, including all well-differentiated tumors). Abstract : Supplemental Digital Content is available in the text.